Carbon and alkalinity outwelling across the groundwater‐creek‐shelf continuum off Amazonian mangroves. Issue 6 (23rd September 2021) - Cabral, Alex; Dittmar, Thorsten; Call, Mitchell; Scholten, Jan; de Rezende, Carlos E.; Asp, Nils; Gledhill, Martha; Seidel, Michael; Santos, Isaac R.
Abstract: Lateral fluxes (i.e., outwelling) of dissolved organic (DOC) and inorganic (DIC) carbon and total alkalinity were estimated using radium isotopes at the groundwater, mangrove creek, and continental shelf scales in the Amazon region. Observations of salinity and radium isotopes in the creek indicated tidally driven groundwater exchange as the main source of carbon. Radium‐derived transport rates indicate that mangrove carbon is exported out of the continental shelf on timescales of 22 ± 7 d. Bicarbonate was the main form (82% ± 11%) of total dissolved carbon in all samples, followed by DOC (13% ± 12%) and CO2 (5% ± 4%). DIC (18.7 ± 15.7 mmol m −2  d −1 ) exceeded DOC (3.0 ± 4.1 mmol m −2  d −1 ) outwelling at all spatial scales. The interpretation of outwelling across the mangrove‐ocean continuum is related to the spatial and temporal scales investigated. At all scales, outwelling represented a major coastal carbon pathway driving bicarbonate storage in the ocean.